A Simple Model of the Taxable and Tax-Exempt Yield Curves - Green, Richard C. (Review of Financial Studies, 1993)
I examine the anomalous behavior of the taxable and tax-exempt yield curves. Long municipal yields appear too high relative to the equivalent after-tax yield that can be earned in Treasury or corporate bonds. I discuss existing explanations of the problem and propose a simple model that relates the yields of taxable bonds to the yield curve for par tax exempts. The ratio of the tax-exempt yield to the taxable yield increases with maturity in the model, so it is consistent with observed phenomena such as inverted yield curves for taxables and contemporaneous rising yield curves for tax exempts. Statistical and descriptive comparisons between the yields predicted.by the model and observed yields on par bonds that the model has some promise in explaining the apparent anomalies in the behaviors of the two yield curves. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.